Shared Services of Selected Companies in Metro Manila: An Operational Efficiency Benchmark - Serraon, Jose Carlo (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study evaluates the operational efficiency of shared services among selected logistics companies in Metro Manila with the objective of establishing an operational efficiency benchmarking framework across key business functions, namely Logistics and Supply Chain Management, Human Resources, Information Technology, and Business Development. The study employed a descriptive, comparative, and evaluative research design and utilized stratified purposive sampling. Data were collected from 43 managers and supervisors through a validated survey questionnaire and analyzed using descriptive statistics, weighted means, and nonparametric tests, specifically the Kruskal–Wallis H Test and the Mann–Whitney U Test, to determine significant differences in shared service evaluations and operational challenges across functional areas. The findings revealed that shared services across all four functions were perceived as “very evident” in terms of effectiveness. High levels of performance were observed in cost optimization, operational flexibility, robustness of information technology infrastructure, and stakeholder alignment. However, gaps were identified in recruitment alignment, proactivity in the adoption of new technologies, and responsiveness to market and industry trends. Logistics and Supply Chain Management emerged as the highest-performing function, while Business Development received the lowest, though still favorable, evaluation. Despite strong performance ratings, operational challenges were consistently observed across all functions, with Logistics and Supply Chain Management experiencing the most pronounced challenges. Overall, the results indicate that shared services contribute to economies of scale, improved service quality, and strategic business growth, while also revealing opportunities for innovation, process optimization, and continuous improvement. The study supports Sustainable Development Goal (SDG) 8 on Decent Work and Economic Growth and SDG 9 on Industry, Innovation and Infrastructure by demonstrating how efficient shared service models enhance productivity and organizational performance in logistics firms. Its sustainability impact lies in strengthening institutional efficiency, operational resilience, and long-term competitiveness through standardized processes and continuous performance benchmarking.
Keywords: Benchmarking; Logistics; Supply Chain; Metro Manila; Operational Efficiency; Shared Services